Recepção de telenovelas, mediações sociopolíticas e gênero - Barbiero, Hellen Panitz (2018)
This research is a study about a reception of telenovelas with 5 women that are integrated in an Organized Association based on principles of Solidarity Economy. The interviewed are between 39 and 65 years old and live in Santa Maria/RS. The objective of this work is to investigate how the Association and Family sociopolitical mediations conform the use the receptors make of the representations about gender in the telenovela concerning the construction of femininity. Which directions the telenovela acquires, articulated with women‘s sociality, have been comprehended here, in the identifications and questionings realized by them about the representations of female in the scope of gender relations. Theoretical and methodologically, the perspective of the Latin American Cultural Studies and the model of Cultural Communicative Mediations (MARTÍN-BARBERO, 2002) have been adopted, in terms of discussion about the possible totality for reception (RONSINI, 2011). It has been analyzed the sociality mediations through the investigation of meanings and Association and family relationships, of rituality, through ways of seeing and interpreting the telenovelas and touched the female representations in the narrative of telenovelas to encompass the technicality. The techniques used for data collection were: participant observation (PERUZZO, 2006) with a field diary, semi-structured interview (VILELA, 2006) and the text in action (WOOD, 2008a; 2008b). The participation in the Association increases the social capital, which takes them to be aware of common problems to other women and the enhancement to the exercise of principles of solidarity and cooperation. The conservative education they have received regarding to gender relations it presents signs of weakening, mainly concerning the teaching they pass to their children – marked by the incentive to the equal division of tasks, by studying and working as a way of independence, by combating violence against women and by sexual education. In families, it is current the working social division based on gender, which is questioned in meetings at Association, mainly by the president, who has a higher level of education and relation with social movements. The ideal maternity is defended and exercised by them, being legitimized by the uses they perform in telenovelas. They realize it is necessary to value the feminine work and in the telenovelas, they identify themselves with characters considered to be workers, questioning the behavior of those who are not. They disapprove behaviors and the nature of vulgar women and they admire the beauty and the behavior of those sensual women, which confirms in the interpretation of the telenovelas. According to their experiences, these women give signals of endorsement to equal affective relationships and a clue of this partial conquest of autonomy is a projection and/or identification with feminine characters who react to violence, as well as the criticism to men and characters considered chauvinist. In general, it has been inferred that the advances regarding to perceptions and experiences in gender relationships more egalitarian can be more discreet, but are increasing. The telenovelas provide the creation of a space-time of sociability permeated by representations about gender which allow women to discuss equalities and inequalities between men and women in their homes and in the Association.